Human-Centered Digital Housing Information and Transaction-Stage Purchase Decisions in Government-Subsidized Housing: Evidence from Lampung, Indonesia - Trian Hermawan; Novita Sari; Anggalia Wibasuri (Women, Education, and Social Welfare, 2026)
This study aims to examine the association between human-centered digital marketing strategy and transaction-stage purchase decisions for government-subsidized housing in Lampung, Indonesia. A cross-sectional quantitative survey involved 100 purposively selected adults who had been exposed to housing information through digital channels and had reached a formal transaction stage, namely a subsidized mortgage application, booking-fee or down-payment payment, or completed purchase. A 40-item questionnaire measured perceived digital marketing strategy and consumer purchase decision. Item-total correlations supported item screening, and internal consistency was high for digital marketing strategy (α = 0.942) and purchase decision (α = 0.936). Regression assumptions were met. Digital marketing strategy was positively associated with purchase decision (B = 0.869, β = 0.968, t = 38.406, p < 0.001), and the model accounted for 93.8% of score variance (R² = 0.938). The findings position digital housing communication as a human-centered welfare service when it improves information clarity, credibility, responsiveness, and access across platforms. Because the data were cross-sectional, self-reported, and purposively sampled, the result is associational rather than causal.